2021
DOI: 10.1007/s13369-021-05956-2
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Lightweight Deep Neural Network for Diagnosis of COVID-19 from Chest X-ray Images

Abstract: Coronavirus (COVID-19) is an epidemic that is rapidly spreading and causing a severe healthcare crisis resulting in more than 40 million confirmed cases across the globe. There are many intensive studies on AI-based technique, which is time consuming and troublesome by considering heavyweight models in terms of more training parameters and memory cost, which leads to higher time complexity. To improve diagnosis, this paper is aimed to design and establish a unique lightweight deep learning-based approach to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…(2) CXR-based classification: The DenseNet201 reports 98.55%, 97.13%, 97.07%, 99.04%, 97.10%, and 98.05% respectively. The accuracy achieved in this study is comparable to the accuracies reported in other studies that used CXR images, such as Ahmadian et al [9] , Ardakani et al [33] , Khan et al [34] , Rajawat et al [35] , Swarup and Anupam [10] , and Ranjan et al [39] . The study also used a CNN-based model, which is a commonly used model for image classification tasks.…”
Section: Experiments and Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…(2) CXR-based classification: The DenseNet201 reports 98.55%, 97.13%, 97.07%, 99.04%, 97.10%, and 98.05% respectively. The accuracy achieved in this study is comparable to the accuracies reported in other studies that used CXR images, such as Ahmadian et al [9] , Ardakani et al [33] , Khan et al [34] , Rajawat et al [35] , Swarup and Anupam [10] , and Ranjan et al [39] . The study also used a CNN-based model, which is a commonly used model for image classification tasks.…”
Section: Experiments and Discussionsupporting
confidence: 87%
“…The average accuracy of the ensemble CNN of 96.51% was recorded. Ranjan et al [39] introduced a lightweight DL LW-CBRGPNet model for COVID-19 multi-class and binary classification using CXR images. The proposed model used CNN architecture and training from scratch without feature extraction.…”
Section: Related Studiesmentioning
confidence: 99%
“…e majority of young people, slightly more than half, become infected with IAV and develop respiratory tract symptoms; the other half either does not develop symptoms or does not get infected at all when given a controlled IAV exposure [6][7][8]. e fact that in uenza has such a substantial in uence on the economy and peoples' health [9][10][11] makes it imperative to predict who will become ill and when. If IAV-infected people are not identi ed and treated promptly, the number of deaths will rise as a result of increased viral transmission and, possibly, worsening of sickness [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The use of ML methods has witnessed a significant rise in health science, particularly in areas such as diagnosis, predicting mortality and case numbers during pandemics, and more. [18][19][20][21][22][23][24] The application of ML algorithms in the health sector has become imperative for health organizations in terms of patient interventions and public warnings. A growing body of recent research reflects the increasing interest in ML within healthcare.…”
Section: Adoption Of Machine Learning In Health Sciencementioning
confidence: 99%
“…The study by Nayak et al 19 focuses on adopting a deep feedforward NN method for diagnosing COVID‐19 using chest x‐ray images. Medeiros et al 25 utilize deep learning (DL) methods to predict glaucoma, a disease leading to blindness.…”
Section: Related Workmentioning
confidence: 99%